ChemInform Abstract: Toward Functional Nanocomposites: Taking the Best of Nanoparticles, Polymers, and Small Molecules. Issue 24 (23rd May 2013) - Kao, Joseph; Thorkelsson, Kari; Bai, Peter; Rancatore, Benjamin J.; Xu, Ting
Abstract Review: 275 refs.